SRC plays a specific role in the cross-talk between apoptosis and autophagy via phosphorylation of a novel regulatory site on AMPK - Ming Zhao; Darren Finlay; Robert Liddington; Kristiina Vuori (Autophagy Reports, 2022)
Cell detachment from the extracellular matrix (ECM) typically promotes cell death via a form of apoptosis known as anoikis. However, in tumor cells, detachment can also induce cell survival, utilizing a process known as macroautophagy/autophagy, which involves degradation and removal of apoptotic proteins as well as rewiring of metabolic pathways so that cells can survive under stress. The crosstalk between the competing processes of anoikis and autophagy is only partially understood but may be critical for the design of multi-drug therapeutic strategies. Here, we summarize our recent studies, which reveal a direct regulatory link between a major mediator of cell survival in adherent cells, the ECM-integrin-activated dual tyrosine kinase complex of SRC and PTK2/FAK, and a major regulator of cell metabolism and autophagy, AMP-activated protein kinase (AMPK). We identify a novel SRC phosphorylation site on AMPK and demonstrate that this phosphorylation event plays key roles in AMPK regulation, autophagy induction, and cell survival.